Experimental Study on Glass Deformation Calculation Using the Holographic Interferometry Double-Exposure Method - Yucheng Li; Yang Zhang; Deyu Jia; Song Gao; Muqun Zhang (Applied Sciences)
This study systematically compares the metrological characteristics of single- exposure, double-exposure, and continuous-exposure holographic interferometry for micro-deformation detection. Results demonstrate that the double-exposure method achieves optimal balance across critical performance metrics through its ideal cosine fringe field modulation. This approach (1) eliminates object wave amplitude interference via dual-exposure superposition, establishing submicron linear mapping between fringe displacement and deformation amplitude; (2) introduces a fringe gradient-based direction detection algorithm resolving deformation vector ambiguity; and (3) implements an error-compensated fusion framework integrating theoretical modeling, MATLAB 2015b simulations, and experimental validation. Experiments on drilled glass samples confirm their superior performance in terms of near-ideal fringe contrast (1.0) and noise suppression (0.06). The technique significantly improves real-time capability and anti-interference robustness in micro-deformation monitoring, providing a validated solution for MEMS and material mechanics characterization.